Transitions in Segmented Labor Markets The Case of Brazil - Woltermann, Silke (Goettinger Studien zur Entwicklungsoekonomik / Goettingen Studies in Development Economics, 2018)
When labor market economists started to work on segmented labor markets, they classified informal employment as a transitory state. At the end of the 20<UP>th</UP> century, informal employment still persists governments' attempts to eradicate it and represents a growing labor market segment not only in developing countries but worldwide. It is evident that informal employment will not disappear but has to be taken into account when designing labor market policies. This study investigates the role of informal dependent employment on the allocation of workers into formal employment in general and on the choice of job search channels in particular. The empirical analysis is based on Cox proportional hazard models and multinomial logistic regression, using Brazilian labor market panel data.